2000
DOI: 10.1046/j.1365-201x.2000.00753.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related differences in twitch contractile properties of plantarflexor muscles in women

Abstract: This study compared maximal voluntary isometric strength and electrically evoked twitch characteristics of the plantarflexor muscles among the groups of women of the 3rd (n=14), 4th (n=13), 5th (n=11), 6th (n=12) and 8th (n=13) decade. A significant decrease (P < 0.05-0.001) has been found in isometric maximal voluntary contraction (MVC) force from the 5th decade and in twitch maximal force from the 6th decade. The 3rd decade group produced 72% greater MVC force and 43% greater twitch maximal force than the 8t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 36 publications
2
14
0
2
Order By: Relevance
“…We observed that the maximal force generating capacity of the knee extensors assessed as either MVC or PT was significantly reduced with age, which is in agreement with previous studies examining other muscle groups (Vandervoort & McComas, 1986; Doherty et al, 1993; Pääsuke et al, 2000). In our study, the reductions in MVC and PT were 29% and 26%, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We observed that the maximal force generating capacity of the knee extensors assessed as either MVC or PT was significantly reduced with age, which is in agreement with previous studies examining other muscle groups (Vandervoort & McComas, 1986; Doherty et al, 1993; Pääsuke et al, 2000). In our study, the reductions in MVC and PT were 29% and 26%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…All data reported were obtained following a thorough familiarization session conducted approximately 1 week before the first test session, which involved subjects performing the evoked twitch assessment and MVC protocols used during testing. The sample size employed in this study is sufficient for assessing measurement reproducibility as the number of subjects involved is highly comparable with previous studies examining evoked twitch properties and neuromuscular adaptations to resistance training (Alway et al, 1989; Rice et al, 1993; Roos et al, 1999; Pääsuke et al, 2000).…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…The conclusion that ''…ability to exert both isometric and dynamic peak force shares some structural and functional foundation with the ability to generate force rapidly'' (Haff et al 1997;p 269) was based on the positive relationship observed between RFD and maximum force recorded under both isometric and dynamic conditions. F max and RFD increase at a similar rate with maturation (Paasuke et al 2001), but decrease with fatigue (Zhou et al 1996) or aging (Paasuke et al 2000). Finally, the well known differences in F max observed between eccentric and isometric force production are also associated with similar differences in RFD (Pryor et al 1994).…”
Section: Relationships Among Muscle Strength Testsmentioning
confidence: 82%
“…Essa redução associada ao declínio da velocidade da contração muscular são as maiores causas de debilidade funcional em idosos 2 . Adicionalmente, estudos têm demonstrado que a habilidade de gerar força rapidamente pode ser mais funcionalmente relevante do que a capacidade de gerar força máxima 3,4 , uma vez que muitas das atividades da vida diária são caracterizadas pelo limitado tempo de desenvolvimento de força (50-200ms), o qual é consideravelmente menor do que o necessário para alcançar a força máxima (≥ 300 ms) 5 .…”
Section: Introductionunclassified